2014
DOI: 10.18632/oncotarget.1896
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A signaling is activated in advanced stage of squamous cell carcinoma of head and neck cancer and requires osteopontin to stimulate invasive behavior

Abstract: The clinical significances, cellular effects, and molecular mechanisms by which Aurora-A mediate its invasive effects in HNSCC are still unclear. Here, we found that Aurora-A expression is significantly higher in tumor tissues on 14-microarray of HNSCC in Oncomine-databases. The activity of Aurora-A was not only found in HNSCC specimens, but also significantly correlated with advanced-T-classification, positive-N-classification, TNM-stage and the poor 5-year survival rate. HNSCC-microarray profile showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…OPN has been studied as a potential therapeutic target in the regulation of cancer metastasis [ 39 41 ]. Activation of a CD44-dependent OPN/Aurora-A/ERK1/2 pathway has been reported, and OPN-activated Aurora-A has been proposed as a potential therapeutic target in head and neck squamous cell carcinoma [ 42 ]. Moreover, expression of OPN at histologically-negative surgical margins has been associated with higher recurrence of oral squamous cell carcinomas and, therefore, may be useful as a prognostic marker of recurrence [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…OPN has been studied as a potential therapeutic target in the regulation of cancer metastasis [ 39 41 ]. Activation of a CD44-dependent OPN/Aurora-A/ERK1/2 pathway has been reported, and OPN-activated Aurora-A has been proposed as a potential therapeutic target in head and neck squamous cell carcinoma [ 42 ]. Moreover, expression of OPN at histologically-negative surgical margins has been associated with higher recurrence of oral squamous cell carcinomas and, therefore, may be useful as a prognostic marker of recurrence [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MER‐Erk1/2 and PI3K/Akt pathway could induced by FAK . Activation of osteopontin‐Aurora‐A‐Erk signaling is associated with progression, especially invasive capacity in head and neck squamous cell carcinoma . Furthermore, we found p‐AURKA upregulation could increase the level of p‐Erk1/2 and p‐AURKA downregulation could decrease the level of p‐Erk1/2.…”
Section: Discussionmentioning
confidence: 68%
“…Previous reports have indicated that either Aurora-A or FLJ10540 involves in multiple signaling pathways to promote cancer progression [ 12 , 13 , 15 , 17 , 24 , 25 ]. Intersection of these pathways elicited by either Aurora-A or FLJ10540, we found that these two molecules have shared common signal pathways for subsistence of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous data indicated that FLJ10540 could form a complex with PI3K for promoting tumor growth in HCC [ 16 ]. Recently, we had demonstrated that Aurora-A was activated in advanced stage of squamous cell carcinoma of head and neck cancer [ 12 ]. In addition, FLJ10540 expression was correlated with aggressiveness of oral cavity squamous cell carcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%